2008
DOI: 10.1007/s10765-008-0511-0
|View full text |Cite
|
Sign up to set email alerts
|

Solid–Liquid Equilibria for the CO2 + R23 and N2O + R23 Systems

Abstract: A recently built experimental set-up was employed for the estimation of the solid-liquid equilibria of alternative refrigerant systems. In this paper two binaries, i.e., carbon dioxide + trifluoromethane (CO 2 + R23) and nitrous oxide + trifluoromethane (N 2 O + R23), were studied down to temperatures of 117 K. In order to check the reliability of the apparatus, the triple points of the pure fluids contained in the mixture were measured, revealing good consistency with the literature.The results obtained for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The experimental isochoric and SLE data were obtained by experimental apparatuses presented elsewhere. [1][2][3][4][5][6][7][9][10][11][12][13][14] The information on the SLE data measurements along with the VLE data for corresponding binaries measured by the isochoric method is presented in Table 1. From the Table 1, it is easily evident that the temperatures of isochoric PVTx in two-phase region data are covering a higher temperature range than SLE data for which, obviously, the upper limit of temperature corresponds to the melting temperature of the solute or solvent, whatever is higher.…”
Section: Experimental Data Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental isochoric and SLE data were obtained by experimental apparatuses presented elsewhere. [1][2][3][4][5][6][7][9][10][11][12][13][14] The information on the SLE data measurements along with the VLE data for corresponding binaries measured by the isochoric method is presented in Table 1. From the Table 1, it is easily evident that the temperatures of isochoric PVTx in two-phase region data are covering a higher temperature range than SLE data for which, obviously, the upper limit of temperature corresponds to the melting temperature of the solute or solvent, whatever is higher.…”
Section: Experimental Data Discussionmentioning
confidence: 99%
“…The experimental SLE results showed that the presented CO 2 + and N 2 O HFCs binaries form the eutectic. In the above-mentioned papers, the eutectic points (temperature and composition) were estimated from a graphical interpretation of the liquidus. The accuracy of the method depends on the shape of the liquidus curve and on the experimental data point distribution; hence, in this paper previous estimates are re-evaluated.…”
Section: Experimental Data Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower temperatures needed in some applications can be achieved by using blends. That is why we recently turned our attention to (carbon dioxide and nitrous oxide) + hydrofluorocarbon (HFC) mixtures as potentially suitable working fluids in low-temperature refrigeration applications.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our lab measured the SLE of several (CO 2 and N 2 O) + HFC binary systems. To study the behavior of the binary systems in terms of the Raoult’s and Dalton’s laws, the PVTx of CO 2 + R41 and N 2 O + R41 were recently studied by the same lab with isochoric and Burnett apparatuses, but no information on the SLE of both title systems is available in the literature. The present study was also undertaken to fill this gap.…”
Section: Introductionmentioning
confidence: 99%